The Influence of Product Quality and Promotion on Purchase Decisions: A Study of a Fashion Store in Bandung - Tiwi Ratna Wulandari; Boy Suzanto; Bulan Tati Fitria; Dhea Perdana Coenraad (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
The occurrence in clothes retailers in Bandung indicates subpar product quality and inadequate promotion, which influences consumer purchase decisions.  This study intends to examine the influence of product quality and advertising on purchase decisions in apparel stores in Bandung since various factors contribute to this situation.  This study employs a quantitative methodology utilizing a survey technique by disseminating questionnaires to individuals who have purchased items at the clothes store.  Statistical software analyzes data and examines the relationships among the researched variables.  The study's findings indicate that product quality has a more significant impact on consumer purchasing decisions than promotion.  Beyond direct influence, product quality exerts an indirect effect via promotion, hence amplifying its impact on purchasing decisions.  Simultaneously, advertising directly affects purchasing decisions and correlates with product quality.  The significant impact of product quality and advertising on purchasing decisions indicates that these elements are crucial in influencing customer behavior.  Nonetheless, additional factors external to this study also affect purchasing decisions, albeit to a lesser extent.  In light of these findings, apparel retailers in Bandung should prioritize enhancements in product quality by emphasizing material standards, design, and durability to align more closely with consumer preferences.  Furthermore, it is essential to employ more imaginative and focused advertising techniques to capture the interest of potential buyers and enhance client loyalty.  Integrating enhanced product quality and efficient promotional tactics is anticipated to influence future purchasing decisions positively.